The architecture of the sports tribunes of the Second Polish Republic in the interwar period, 1919−1939 - Kocki, Wojciech (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2022)
The tribunes are a group of sports facilities accompanying many sports facilities of various disciplines. These objects had many types of architectural forms, from small-scale wooden structures, through medium-sized steel structures, to large brick and reinforced concrete structures. The tribunes, depending on the rank of the sports facility, were designed as open or roofed. In some buildings, the function of the audience was combined with the back of sanitary rooms, cloakrooms, cash registers, entrances, restaurants, etc. Many of these buildings played a representative role. The stands built in the interwar period were one of the first facilities of this type. The later projects of the tribunes referred in their function and form to the examples from the Second Polish Republic.